Sabrina [videorecording (Blu-Ray)] - Wilder, Billy, 1906-2002; Taylor, Samuel, 1912-2000; Lehman, Ernest, 1915-2005; Taylor, Samuel, 1912-2000; Ford, Harrison, 1942-; Ormond, Julia; Kinnear, Greg, 1963- (Kino Lorber, 2026)
This 1990s update of the play Sabrina Fair and its 1954 Billy Wilder adaptation was directed by Sydney Pollack (3 Days of the Condor, Tootsie) and shimmers like a fairy tale. Ford plays Linus Larrabee, a busy tycoon who has no room for love in his appointment book. But when a romance between his playboy brother and Sabrina, daughter of the family chauffeur, threatens one of Linus' business deals, the CEO clears his schedule for some ruthlessness. He courts Sabrina, intending to drop her when the deal closes. Will 'the world's only living heart donor' discover his heart? Of course! But, like the best journeys, the fun isn't just the destination, it's the getting there.